Cost-effectiveness of bazedoxifene versus raloxifene in the treatment of postmenopausal women in Spain - Darbà J; Pérez-Álvarez N; Kaskens L; Holgado-Pérez S; Racketa J; Rejas J (Dove Medical Press, 2013)
Josep Darbà,1 Nuria Pérez-Álvarez,2 Lisette Kaskens,2 Susana Holgado-Pérez,3 Jill Racketa,4 Javier Rejas5 1Universitat de Barcelona, Barcelona, Spain; 2BCN Health Economics and Outcomes Research, Barcelona, Spain; 3Hospital Universitari Germans Trias i Pujol, Badalona, Barcelona, Spain; 4Global Health Economics and Outcomes Research, Pfizer Inc., Collegeville, PA, USA; 5Health Economic and Outcomes Research Department, Pfizer Alcobendas, Madrid, Spain Background: The purpose of this study was to assess the cost-effectiveness of bazedoxifene and raloxifene for prevention of vertebral and nonvertebral fractures among postmenopausal Spanish women aged 55–82 years with established osteoporosis and a high fracture risk. Methods: A Markov model was developed to represent the transition of a cohort of postmenopausal osteoporotic women through different health states, ie, patients free of fractures, patients with vertebral or nonvertebral fractures, and patients recovered from a fracture. Efficacy data for bazedoxifene were obtained from the Osteoporosis Study. The perspective of the Spanish National Health Service was chosen with a time horizon of 27 years. Costs were reported in 2010 Euros. Deterministic results were presented as expected cost per quality-adjusted life-year (QALY), and probabilistic results were represented in cost-effectiveness planes. Results: In deterministic analysis, the expected cost per patient was higher in the raloxifene cohort (€13,881) than in the bazedoxifene cohort (€13,436). QALYs gained were slightly higher in the bazedoxifene cohort (14.56 versus 14.54). Results from probabilistic sensitivity analysis showed that bazedoxifene has a slightly higher probability of being cost-effective for all threshold values independent of the maximum that the National Health Service is willing to pay per additional QALY. Conclusion: Bazedoxifene was shown to be a cost-effective treatment option for the prevention of fractures in Spanish women with postmenopausal osteoporosis and a high fracture risk. When comparing bazedoxifene with raloxifene, it may be concluded that the former is the dominant strategy. Keywords: osteoporosis, bazedoxifene, raloxifene, vertebral, nonvertebral, fracture, efficacy, costs